Trends in Ornamental Plant Production - Salachna, Piotr (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The available range of ornamental plants (cut flowers, potted plants, perennials, bulbous, woody ornamental plants) is constantly being supplemented with new species and cultivars; thus, new methods for their production are required. The sustainable development of the floriculture industry requires modern and environmentally friendly solutions that can maximize the plant's potential. Therefore, it is necessary to adapt flower production methods to actual conditions and take into account the energy transformation and biological, technical, and organizational advances. This Special Issue is a collection of seven well-written research works covering the current state-of-the-art of ornamental crop production. The main body of the Special Issue gives an interesting coverage of new strategies that can be utilized for plant reproduction, regulating their growth and flowering, adapting production technologies to fit the concept of sustainable development, and optimizing supply chain management. This Special Issue will provide a good reference source for growers, research scientists, and advanced undergraduate students.